Mahmudah, S STUDI TENTANG KEPUASAN DAN BEHAVIORAL INTENTIONS MAHASISWA POLITEKNIK NSC SURABAYA (JBT (JURNAL BISNIS dan TEKNOLOGI), 2014)
The purpose of this study are: 1) to describe the students’ satisfaction at NSC Polytechnic Surabaya, 2) to describe the students’ behavioral intentions (intentions to leave) at NSC Polytechnic Surabaya, and 3) to explain the effect of satisfaction on students' behavioral intentions (intentions to leave) at NSC Polytechnic Surabaya. The method used to achieve those goals was explanatory with descriptive and inferential analysis. Inferential analysis is performed using a simple linier regression with SPSS program version 19. Data were taken from 115 students of Business Administration, Accounting, Hospitality, and Computer Engineering Department with questionnaire who has been taking classes at least one semester using disproportioned stratified random sampling techniques. Questionnaires were filled with a total of 88 respondents (response rate 76.5%) and 86 questionnaires were analyzed. The results showed that: 1) the students’ satisfaction is high (mean 3.71); 2) the student’s behavioral intentions (intentions to leave) is low (mean 2.19); and 3) the students’s satisfaction has a negative significant effect on behavioral intentions (intentions to leave) with a determination coefficient of 24.3%. It means, the higher the student's satisfaction, the lower the students' intentions to leave at NSC Polytechnic Surabaya.